Rheumatoid Hand Surgery: Is there a Decline? A 22-Year Population-Based Study. (June 2015) - Gogna, Rajiv; Cheung, Graham; Arundell, Melanie; Deighton, Chris; Lindau, Tommy R.
Background: Rheumatoid arthritis (RA) is the most common idiopathic inflammatory arthritis affecting 0.8 % of the population. It can cause significant hand and wrist damage and dysfunction. Recent advances in anti-rheumatic treatments have the potential to decrease the prevalence of hand deformities in patients with RA. Our aim was to investigate whether there has been a decline over 22-years in the number of hand surgical procedures being undertaken for patients with RA and whether this correlates with the introduction of new anti-rheumatic therapies. Methods: We performed a retrospective, population-based (Derbyshire) study of all patients with RA who underwent hand surgery at the Pulvertaft Hand Centre from 1990 to 2012. Index procedures included (1) teno-synovectomy and soft tissue procedures, (2) wrist arthrodesis/arthroplasty and (3) finger arthrodesis. Results: A total of 297 procedures were performed in 153 Derbyshire patients with RA over the 22-year period, with mean age at surgery 59 years (range 24–88 years). The female to male ratio was 2.5:1. The overall trend showed a peak in 2004 and a subsequent decline thereafter. This coincides with an increasing tendency by local rheumatologists to introduce earlier and more intensive conventional disease-modifying drugs and biological therapies for more resistant disease. Conclusions: There has been a decline in the number of hand surgery procedures being performed on patients with RA during our 22-year population-based study. It indicates that medical treatments and strategies have been successful at preventing disease progression.